2016
DOI: 10.1016/j.nanoen.2015.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Nano-pathways: Bridging the divide between water-processable nanoparticulate and bulk heterojunction organic photovoltaics

Abstract: Here we report the application of a conjugated copolymer based on thiophene and quinoxaline units, namely poly[2,3-bis-(3-octyloxyphenyl)quinoxaline-5,8-diyl-altthiophene-2,5-diyl] (TQ1), to nanoparticle organic photovoltaics (NP-OPVs). TQ1 exhibits more desirable material properties for NP-OPV fabrication and operation, particularly a high glass transition temperature (T g) and amorphous nature, compared to the commonly applied semicrystalline polymer poly(3-hexylthiophene) (P3HT). This study reports the opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
135
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(142 citation statements)
references
References 44 publications
7
135
0
Order By: Relevance
“…This level of performance is comparable to optimized NP solar cells from other materials. 22,23,25,33,3537 For the NP cells with [70]PCBM as acceptor, we found a similar trade-off between an increasing J SC and decreasing FF for thicker films (Table 6) as that found for [60]PCBM (Table 3). The reduction in FF for thicker layers is attributed to increased bimolecular recombination.…”
Section: Results and Discussionsupporting
confidence: 71%
“…This level of performance is comparable to optimized NP solar cells from other materials. 22,23,25,33,3537 For the NP cells with [70]PCBM as acceptor, we found a similar trade-off between an increasing J SC and decreasing FF for thicker films (Table 6) as that found for [60]PCBM (Table 3). The reduction in FF for thicker layers is attributed to increased bimolecular recombination.…”
Section: Results and Discussionsupporting
confidence: 71%
“…33,43,50 Thus, precise control over the thermal annealing temperature is crucial to achieve a homogenous active layer in OPVs as well as removing the moisture and avoiding large phase separation. 37 Similar behaviour was also found in the case of NP-xylene films, when annealed at different temperatures ( Fig. 4e-h).…”
supporting
confidence: 82%
“…The size distribution of PTNT:PC 71 BM (1:2 weight ratio) NPs prepared from different organic solvents were characterized from SEM images with a circular Hough transform algorithm. [37][38] In the varied annealing temperature study, all films were predried at 90 °C for 4 min immediately after spin-coating for consistency with device fabrication.…”
Section: Nanoparticle Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] Various studies on NP-OPV active layers revealed some of the factors influencing their morphology. [17] Similarly, D'Olieslaeger et al [18,19] suggested that, in the case of some low band gap (LBG) polymers, higher annealing temperature of around 180 °C are required to prepare efficient devices. [17] Similarly, D'Olieslaeger et al [18,19] suggested that, in the case of some low band gap (LBG) polymers, higher annealing temperature of around 180 °C are required to prepare efficient devices.…”
Section: Introductionmentioning
confidence: 99%